Introduction to engineering materials - John, V.B. (New York, NY: MacMillan Publishing Company, 1983)
A text which deals with the basic principles of materials science and technology in a simple, yet thorough manner. This edition includes more worked examples and more detailed information on certain aspects of materials science.
Part 1 The materials of engineering. Part 2 Materials science: atomic structure and bonding; influence of bond type on structure and properties; the formation of polymers; crystalline structures; glasses and partial crystallinity; elastic behaviour; dislocations and plasticity in metals; viscoelasticity; toughness and fracture of materials; phase diagrams and alloy formation; phase transformations and diffusion; electrical and magnetic properties; optical, thermal and other properties. Part 3 The materials of engineering: non-ferrous metals and alloys; iron and steel; thermoplastics; elastomers; thermosetting materials; ceramics and glasses; composite materials. Part 4 Forming and fabrication of materials: forming processes for metals; forming processes for polymer materials; forming processes for ceramics and glasses; material removal processes; joining processes. Part 5 Behaviour in service: failure, fatigue and creep; oxidation, corrosion and other effects. Part 6 Evaluation of materials: property testing; non-destructive testing; macro- and micro-examination; materials selection.
Includes index
Keywords: Materials